Retrospective outcome in women aged 45 years and older undergoing natural cycle IVF treatment. Issue 1 (July 2021) - Fujishiro, Emi; Yoneyama, Koichi; Kakinuma, Toshiyuki; Kagawa, Aiko; Tanaka, Rieko; Kaijima, Hirotsune
Highlights: The live birth rate per fresh embryo transfer were 0.8% (7/900) under natural cycle IVF. Natural cycle IVF treatment led to seven successful deliveries. All seven women were poor ovarian responders who met the Bologna criteria. Among them, three had elevated serum FSH levels at day 3 (range: 39.0–47.1 mIU/mL). Day 3 FSH levels were not associated with a positive pregnancy. Abstract: Research question: Is natural cycle IVF treatment beneficial to middle-aged women with poor ovarian response? Design: Retrospective investigation of outcomes in women aged 45 years and older, who underwent natural cycle IVF treatment between 2009 and 2018 in a single assisted reproduction clinic with the aim of reporting several successful outcomes. Results: In total, 2408 IVF retrievals in women aged 45 years and older were included in this study. Mean serum FSH level on day 3 was 21.4 ± 12.5 (range: 0.3–93.7) IU/ml. One fresh cleavage-stage embryo was transferred in 37.4% (900/2408) of the initiated cycles. The overall clinical pregnancy rate and live birth rate per fresh embryo transfer were 2.8% (25/900) and 0.8% (7/900), respectively. Natural cycle IVF treatment led to seven successful deliveries during the period. All seven women who successfully delivered were poor ovarian responders who met the diagnostic Bologna criteria and, among them, three had elevated serum FSH levels on day 3 (range: 39.0–47.1 mIU/ml). All seven had full-term delivery, and no congenital abnormalities were observed in their infants. No significant difference was found in serum FSH level on day 3 between those with and without positive beta-HCG test results. Conclusions: These findings suggest that natural cycle IVF treatment could be an option for older poor responders in countries that do not permit egg donation. Careful counselling is required, however, because of the low probability of live births after IVF in middle-aged women.